2003
DOI: 10.1128/jvi.77.10.5784-5793.2003
|View full text |Cite
|
Sign up to set email alerts
|

Positive Regulation of CXCR4 Expression and Signaling by Interleukin-7 in CD4+Mature Thymocytes Correlates with Their Capacity To Favor Human Immunodeficiency X4 Virus Replication

Abstract: The emergence of X4 human immunodeficiency virus type 1 (HIV-1) variants in infected individuals is associated with poor prognosis. One of the possible causes of this emergence might be the selection of X4 variants in some specific tissue compartment. We demonstrate that the thymic microenvironment favors the replication of X4 variants by positively modulating the expression and signaling of CXCR4 in mature CD4 ؉ CD8؊ CD3 ؉ thymocytes. Here, we show that the interaction of thymic epithelial cells (TEC) with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 64 publications
(68 reference statements)
3
44
2
1
Order By: Relevance
“…Alternatively, it is possible that rIL-7/HGFb acts indirectly on ETPs by increasing the generation of their precursors in the BM and/or by supporting the migration of these precursors to the thymus. This possibility is supported by our observations (8) (L. Lai and I. Goldschneider, unpublished observations) that rIL-7/HGFb markedly enhances hematopoiesis and the generation of common lymphoid progenitors and by reports that rIL-7 and rHGF upregulate chemokine receptors and adhesion molecules on a variety of lymphohemopoietic cells (46)(47)(48)(49)(50). It can similarly be speculated that the effect of rIL-7/HGFb on DP thymocytes is secondary to its stimulation of DN thymocytes.…”
Section: Discussionsupporting
confidence: 74%
“…Alternatively, it is possible that rIL-7/HGFb acts indirectly on ETPs by increasing the generation of their precursors in the BM and/or by supporting the migration of these precursors to the thymus. This possibility is supported by our observations (8) (L. Lai and I. Goldschneider, unpublished observations) that rIL-7/HGFb markedly enhances hematopoiesis and the generation of common lymphoid progenitors and by reports that rIL-7 and rHGF upregulate chemokine receptors and adhesion molecules on a variety of lymphohemopoietic cells (46)(47)(48)(49)(50). It can similarly be speculated that the effect of rIL-7/HGFb on DP thymocytes is secondary to its stimulation of DN thymocytes.…”
Section: Discussionsupporting
confidence: 74%
“…This result contrasts with other studies that describe down-regulation of CXCR4 and CCR5 by IFN-␣ in PBMCs or cell lines and macrophages derived from CD34 ϩ cells from umbilical cord blood, respectively (69,70). Conversely, IL-7 up-regulated CXCR4 expression in T cells, PBMCs, and thymocytes, and this effect was associated with increased susceptibility to infection with X4 HIV strains (28,30,32,37). The disparate results from these and our experiments may be explained by the different experimental systems used.…”
Section: Discussioncontrasting
confidence: 55%
“…Pharmacological doses induce a central renewal and a peripheral expansion of CD4 ϩ and CD8 ϩ T cells in macaques infected with SIV (23,24). However, in vitro, IL-7 enhances HIV replication (2,3,(25)(26)(27)(28)(29)(30)(31)(32). Its effects on HIV replication in SCID-hu mice or SIV-infected monkeys have been inconsistent (23,24,33,34), and IL- 7 has not yet been tested in clinical trials of HIV therapy.…”
mentioning
confidence: 99%
“…No modifications of antiretroviral regimen or compliance issues with antiretroviral drugs were reported in these patients. Recent in vitro studies have shown that IL-7 may increase HIV infectivity of CD4 + T cells (34)(35)(36). With this in mind, we evaluated the cellular content of viral DNA at entry, at 21 d, and at 12 wk.…”
Section: Cd8 + T Cellsmentioning
confidence: 99%